KEBIJAKAN PREVENTIF MUDIRUL AMM’ TERHADAP PELECEHAN SEKSUAL DI LINGKUNGAN PONDOK PESANTREN LOMBOK BARAT - Idul Adnan (STIS Darussalam Bermi, 2025)
This study aims to analyze the factors influencing the occurrence of sexual harassment in Islamic boarding school environments and to examine the preventive policies implemented by the Mudirul ‘Amm in preventing sexual violence. The theoretical framework of this study is grounded in the Theory of Legal Protection, which emphasizes the obligations of the state and educational institutions to safeguard the rights and safety of students, as well as the Theory of Responsibility of Educational Institution Leaders, which positions pesantren leaders as key actors in policy formulation, supervision, and enforcement of internal regulations. This research employs a combination of empirical and normative legal research using a qualitative approach. The normative approach is applied to analyze statutory regulations, institutional policies, and principles of Islamic law related to the protection of students. Meanwhile, the empirical approach is used to examine the implementation of preventive policies in Islamic boarding schools in West Lombok through observation and field data collection. The findings indicate that sexual harassment in pesantren environments is influenced by various interrelated factors, including limited understanding of sexual harassment, inadequate environmental supervision, psychosocial factors and adolescent development, the absence of clear Standard Operating Procedures (SOPs) and reporting mechanisms, internal factors of perpetrators, and insufficient parental support in reporting cases. In response to these conditions, the Mudirul ‘Amm has implemented several preventive policies, including the formulation of anti-harassment regulations and SOPs, strengthening supervisory systems, providing education and guidance for students, enhancing the capacity of teachers and caregivers, and establishing reporting and complaint mechanisms.